Does Internet use help to achieve sustainable food consumption? Evidence from rural China - Jian Liu; Yanjun Ren; Yu Hong; Thomas Glauben; Qiang Li (Sustainable Futures)
Internet use is widely studied as an important socio-economic factor influencing agricultural productivity, income, the adoption of sustainable agricultural practices, and farmer welfare, but scant attention is given to its influence on sustainable food consumption. Using longitudinal data from the China Health and Nutrition Survey (CHNS), this study seeks to better understand the causal effect of Internet use on sustainable food consumption measured by food carbon and food water footprints and shed light on its underlying channels. The instrumental variable estimation is used to solve the endogeneity problem of Internet use and the propensity score matching (PSM) method is used for robustness check. The results show that Internet use significantly decreases food carbon and food water footprints by 18.1 % and 10.6 %, respectively. Internet use promotes the development of sustainable food consumption mainly by reducing the consumption of animal-based food such as pork and eggs. Further heterogeneity analysis results indicate that Internet use mainly affects the sustainable food consumption of young and high-income individuals. Policy implications for reducing food carbon and food water footprints and achieving a win-win situation for consumption and the environment are also discussed.